PENERAPAN REHABILITASI JANTUNG FASE 1 PADA PASIEN SINDROMA KORONER AKUT (SKA) DI RUMAH SAKIT JANTUNG DAN PEMBULUH DARAH HARAPAN KITA JAKARTA - Ridho Kunto Prabowo (JURNAL KESEHATAN INDRA HUSADA, 2019)
Cardiac rehabilitation is all actions taken to optimally improve physical, mental and social functioning to restore functional capacity in patients with life-threatening acute coronary or post-invasive patients. Phase I cardiac rehabilitation is an immediate initiation to carry out cardiac rehabilitation in the acute phase. This study aims to identify the application of phase 1 cardiac rehabilitation in ACS patients. Research using quantitative design with descriptive approach. The research sample consisted of 12 respondents using purposive sampling technique. The results of phase 1 to level 1 to 3 day 5 cardiac rehabilitation studies in patients with ACS obtained Chest Pain, Dyspnea and ECG images whose values ​​were constant or the same for all respondents both at the beginning, exercise and end. It can be concluded that during phase 1 level 1 heart rehabilitation to level 3 days 5 there were no changes in Chest Pain, Dyspnea and ECG in SKA patients. While the difference in heart rate and blood pressure values ​​statistically showed significant, but clinically not significant. Suggestion phase 1 cardiac rehabilitation is a safe action and can be done independently by nurses and therefore must be applied to ACS patients. Keywords: Phase 1 Cardiac Rehabilitation, Acute Coronary Syndrome